2018
DOI: 10.1186/s12934-018-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Module and individual domain deletions of NRPS to produce plipastatin derivatives in Bacillus subtilis

Abstract: BackgroundPlipastatin, an antifungal lipopeptide, is synthesized by a non-ribosomal peptide synthetase (NRPS) in Bacillus subtilis. However, little information is available on the combinatorial biosynthesis strategies applied in plipastatin biosynthetic pathway. In this study, we applied module or individual domain deletion strategies to engineer the plipastatin biosynthetic pathway, and investigated the effect of deletions on the plipastatin assembly line, as well as revealed the synthetic patterns of novel l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The peptide moiety synthesized by these megaenzymes can be short, linear, cyclic, or branched-cyclic. Amino acids modifications such as epimerization, methylation or hydroxylation are frequent, giving place to a vast structural diversity of peptides produced by each Bacillus strain (Gao et al, 2018). Therefore, it is interesting to explore the antimicrobial activities of CLP produced by novel native Bacillus strains.…”
Section: Introductionmentioning
confidence: 99%
“…The peptide moiety synthesized by these megaenzymes can be short, linear, cyclic, or branched-cyclic. Amino acids modifications such as epimerization, methylation or hydroxylation are frequent, giving place to a vast structural diversity of peptides produced by each Bacillus strain (Gao et al, 2018). Therefore, it is interesting to explore the antimicrobial activities of CLP produced by novel native Bacillus strains.…”
Section: Introductionmentioning
confidence: 99%
“…These modules are responsible for incorporating specific amino acids in the molecules and consist of three major catalytic domains: condensation (C), adenylation (A), and thiolation (T) domains. Finally, the last module frequently also contains the thioesterase (Te) domain (Gao et al 2018).…”
Section: Nrps Engineeringmentioning
confidence: 99%
“…The remaining modules, which are adjacent to the deletion, were recombined at different highly conserved sequence motifs that are characteristic of amino acid-incorporating modules of peptide synthetases. Gao et al (2018) stated that the entire deletion of an NRPS module, which was a producer of plipastatin, caused the inactivation of the enzyme. However, the authors observed that individual domain deletion (A and T domains) leads to the creation of three novel plipastatin derivatives.…”
Section: Nrps Engineeringmentioning
confidence: 99%
“…Thalassospiramide assembly lines also catalyze programmed module skipping. Forward module skipping has been previously observed in PKS [26][27][28] and NRPS [29][30][31] systems, both naturally and as a byproduct of assembly line engineering. Ttc and Ttm catalyze analogous skipping of PKS module 1b and NRPS module 2, respectively, although NRPS module 2 does not sit at an enzyme junction but is embedded within a very large polypeptide.…”
Section: Thalassospiramide Assembly Lines Catalyze Several Instances mentioning
confidence: 99%